A multiproxy reconstruction of Hebridean (NW Scotland) spring sea surface temperatures between AD 1805 and 2010 - Reynolds, D. J.; Butler, P. G.; Williams, S. M.; Scourse, J. D.; Richardson, C. A.; Wanamaker, A. D.; Austin, W. E. N.; Cage, A. G.; Sayer, M. D. J. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2013)
There is currently a deficiency of annually-resolved temperature series from the marine environment. We present a multiproxy reconstruction of Hebridean shelf sea (Tiree Passage; NW Scotland) spring sea surface temperatures (SSTs) for the period AD 1805-2010. The reconstruction is based on the growth increment series from the first absolutely dated annually-resolved multi-centennial Glycymeris glycymeris bivalve mollusc sclerochronology coupled with previously published stable oxygen isotope data (delta O-18) from benthic foraminifera sampled from a dated sediment core from nearby Loch Sunart The independent series contain significant correlations with SSTs across complementary frequency domains. The low frequency component of the sedimentary archive was combined with the mid and high frequency components of the G. glycymeris chronology indices to create a single multiproxy series. Split calibration-verification statistics (reduction of error, RE, coefficient of efficiency, CE, and R-2) indicate that the multiproxy record, calibrated to local instrumental sea surface temperatures, contains significant precision and skill at reconstructing spring SSTs (RE = 0.59, CE = 0.26, R-2 = 0.54). These data demonstrate that bivalve sclerochronologies, when combined with low frequency proxies such as sediment archives, can facilitate statistically robust reconstructions of palaeoceanographic variability during the late Holocene for hydrographically-significant regions of the temperate marine system previously void of annually-resolved archives. The reconstructed SSTs contain a general warming trend of 0.60 +/- 0.14 degrees C per century. Only four years in the reconstructed period (1999, 2000, 2002 and 2003) exceed temperatures greater than two standard deviations higher than the reconstructed mean SST (9.03 degrees C), whilst just three years in the first half of the 19th century (1835, 1838 and 1840) fall more than 2 sigma below the reconstructed mean (6.80 degrees C). (C) 2013 Published by Elsevier B.V.